2000
DOI: 10.1063/1.126899
|View full text |Cite
|
Sign up to set email alerts
|

High ε gate dielectrics Gd2O3 and Y2O3 for silicon

Abstract: We report on growth and characterization of both epitaxial and amorphous films Gd2O3 of (ε=14) and Y2O3(ε=18) as the gate dielectrics for Si prepared by ultrahigh vacuum vapor deposition. The use of vicinal Si (100) substrates is key to the growth of (110) oriented, single-domain films in the Mn2O3 structure. Typical electrical leakage results are 10−3 A/cm2 at 1 V for single domain epitaxial Gd2O3 and Y2O3 films with an equivalent SiO2 thickness, teq of 15 Å, and 10−6 A/cm2 at 1 V for smooth amorphous Y2O3 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(138 citation statements)
references
References 15 publications
5
132
0
1
Order By: Relevance
“…However, it also turns out that the thermodynamic data for many oxides was not so accurate. It was subsequently found that ZrO 2 is actually slightly unstable [12,13] [14][15][16][17][18].…”
Section: Thermodynamic Stabilitymentioning
confidence: 99%
“…However, it also turns out that the thermodynamic data for many oxides was not so accurate. It was subsequently found that ZrO 2 is actually slightly unstable [12,13] [14][15][16][17][18].…”
Section: Thermodynamic Stabilitymentioning
confidence: 99%
“…Among several binary earth metal oxides under consideration, Gadolinium sesquioxide, one of the promising substitutes for SiO 2 in ultra-large-scale integration (ULSI), has attracted much attention recently. It has a band gap of 5.3 eV [9,10], and a high dielectric constant of 14-20 [11,12], meaning that a 4.9 nm film can satisfy the requirement of a 1 nm equivalent oxide thickness. Another interesting topic on studying Gadolinium oxide is its structures.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial oxide/Si heterostructures are also of interest as templates for the integration of epitaxial functional materials with Si [2]. Binary insulators with the cubic fluorite structure, and its derivatives, are known to grow epitaxially on (111) oriented Si [3][4][5][6][7][8][9][10]. Oxides with the pyrochlore and bixbyite structures are vacancy-ordered derivatives of the fluorite structure and have lattice parameters that are approximately twice that of Si.…”
mentioning
confidence: 99%